2019
DOI: 10.3390/ijms20102461
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Optical Biosensors

Abstract: Graphene shows great potential in biosensing owing to its extraordinary optical, electrical and physical properties. In particular, graphene possesses unique optical properties, such as broadband and tunable absorption, and strong polarization-dependent effects. This lays a foundation for building graphene-based optical sensors. This paper selectively reviews recent advances in graphene-based optical sensors and biosensors. Graphene-based optical biosensors can be used for single cell detection, cell line, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 141 publications
0
47
0
2
Order By: Relevance
“…The current research focus is to use new structures, new principles, and new methods to improve the sensitivity, responsivity, and compatibility of polarizing devices. Graphene and light interact differently in various photonic and optoelectronic devices, so graphene optical devices need to work under different structures [119]. The polarizing devices that are mentioned in this letter all require strong interaction between graphene and light.…”
Section: Discussionmentioning
confidence: 99%
“…The current research focus is to use new structures, new principles, and new methods to improve the sensitivity, responsivity, and compatibility of polarizing devices. Graphene and light interact differently in various photonic and optoelectronic devices, so graphene optical devices need to work under different structures [119]. The polarizing devices that are mentioned in this letter all require strong interaction between graphene and light.…”
Section: Discussionmentioning
confidence: 99%
“…Graphene plays a significant role in the field of biosensors with extraordinary electrochemical, electrical, magnetic and optical properties [ 170 ]. Graphene features, such as functionalization, high flexibility and optical transmittance, have made possible the recent rise of graphene application in nanosensors [ 171 , 172 ]. Numerous studies indicated the possibility for sensitive detection of PCa biomarkers with graphene structures [ 173 , 174 ].…”
Section: Nanomaterials Towards Diagnosis and Biosensing Of Prostatmentioning
confidence: 99%
“…Optical biosensors and similar bioassays are an extensively researched group of analytical devices, as seen from the recent reviews written in this field [27,28,29,30,31,32,33,34,35,36,37,38]. The optical biosensors also have a long tradition in teams protecting from biological warfare agents because there is a high number of disposable colorimetric tests and portable devices available in the market.…”
Section: Optical Biosensors For Biological Warfare Agents Assaymentioning
confidence: 99%